AN ANALYSIS OF MAXIM FLOUTING IN TV SERIES GAME OF THRONES SEASON 1 - Adithya Lapadjawa; Nurmin Samola; Sarah Kamagi (KOMPETENSI, 2022)
This research aims to analyze the types of maxims that are flouted in Game of Thrones Season 1. The descriptive qualitative method is employed in this research. The data of this research are in the form of utterances from the characters in Game of Thrones that contain maxim flouting. The source of the data is the Game of ThronesTV series and its script. The data are collected through watching the TV series, reading the script, and taking notes of utterances where the maxims are flouted. The results show that all the four types of maxims are flouted by the characters of the TV series with the occurrence of 19 times. The type of maxim that is flouted the most by the characters is the maxim of relation. The characters flout the maxim of relation on nine different occasions. Then, the maxim of quality is ranked second with the frequency of six times. After that, the following maxim of quality is maxim of quantity with three cases. Finally, the least flouted maxim of all four is maxim of manner which only appears one time.